The News Framing of Middle East Conflict Coverage on Metro TV - Rai Bagus Triadi; Tri Pujiati (English Lecturers and Teachers Association (ELTA), 2026)
A compelling phenomenon emerges in the coverage of the geopolitical tensions involving the United States, Israel, and Iran on Metro TV. This conflict is not merely presented as an international event; rather, it is discursively constructed by mass media in ways that may shape public perception. The problem addressed in this study lies in the potential lack of neutrality in media reporting and the presence of implicit framing that influences audience interpretation. Accordingly, the objective of this research is to critically examine how the conflict is framed and represented in Metro TV’s news coverage. This study employs a qualitative approach, utilizing Norman Fairclough’s Critical Discourse Analysis (CDA) framework, which encompasses three levels of analysis: the micro level (textual analysis), the meso level (discursive practice), and the macro level (sociocultural practice). Through this multi-layered analytical lens, the study investigates linguistic features, production processes, and broader socio-political contexts shaping the news narratives. The findings reveal that the coverage is not entirely neutral; rather, it is influenced by editorial perspectives, the selection of sources, and prevailing global political dynamics. The analysis indicates a discernible tendency toward specific framing strategies, particularly in emphasizing security concerns, humanitarian issues, and the positioning of the states involved. These patterns suggest that media discourse plays an active role not only in disseminating information but also in constructing social reality and shaping public opinion. Keywords :media bias, news framing, conflict, Metro TV